PENGARUH PENAMBAHAN LIMBAH PLASTIK BEKAS TERHADAP KARAKTERISTIK KEKUATAN TARIK DAN KEKUATAN BENDING MATERIAL POLIMER KOMERSIL - Sujita, S.; Hadi, S. Gunawan (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2015)
Polyester, epoxy and polyurethane composites are widely used for the matrix. The use of composite materials in the manufacturing industry as well as many studies of composites by utilizing plastic powder and the lack of studies directly comparing the tensile strength and bending properties of composite plastic powder to the treatment of the same fiber. The purpose of this study was to determine the tensile and bending strength of the composite material of polyester, epoxy, and polyurethane with reinforcing plastic powder by varying the volume fraction. In this study, the material used is plastic powder, with a size of 8 mm and the preparation of chopped random fibers, with a fiber volume fraction (0% / 100%, 5% / 95%, 10% / 90%, 20% / 80%, 30 % / 70%, 40% / 60, 50% / 50%, 60% / 40%, and 70% / 30%), using polyester resin, epoxy, and polyurethane as matriknya. Comparison of epoxy resin and polyurethane that is one to one, while for polyester using the catalyst of 2%. Tensile testing with ASTM D 3039, and bending test were conducted with ASTM D 790. The results of tensile testing tensile strength values obtained by variation of the highest volume fraction of 0% is owned by a composite plastic powder with 100% polyester resin with a value of 35.22 MPa, followed by a variation of the volume fraction of the composite with 0% plastic powder with 100% epoxy resin with the strength values pull of 6.40 MPa. While bending test results obtained the highest bending strength values held by the variation of volume fraction of the composite 0% plastic powder with 100% polyester resin with a value of 66.985 MPa, then successively followed by the composite with the highest volume fraction variation possessed by 30% of composite powders plastic with 70% epoxy resin with a value of 42.078 MPa bending strength, for a volume fraction of 50% variation of plastic powder with 50% polyurethane resin to obtain the highest value of bending strength of 6.963 MPa.